Pete the Cat and the Tip-top Tree House - Dean, James 1957- (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2017)
Pete invites his friends over, but when he finds that his tree house is not big enough for everyone, they work together to build a fun place that can house everyone.
Keywords: Pete, -- the Cat (Fictitious character) -- Juvenile fiction; Pete, -- the Cat (Fictitious character) -- Fiction; Cats -- Juvenile fiction; Tree houses -- Juvenile fiction; Friendship -- Juvenile fiction; Cooperativeness -- Juvenile fiction; Cats -- Fiction; Tree houses -- Fiction; Friendship -- Fiction; Cooperativeness -- Fiction